Mini service provider - Terence, Jerome Daim. (Universiti Malaysia Sarawak, UNIMAS, 2006)
Mini Service Provider is a system that will benefit a group of users with the intention to seek an easy method to share resources and services. With the advent of available networking and software development technologies, it is thus the main aim of this project to make this system a reality through proper planning and execution.